A chromo-fluorogenic probe for detecting water traces in aprotic solvents based on C2-symmetry dianthrimide–hydroxide complexes: experimental and theoretical studies. Issue 1 (11th December 2020) - Uahengo, Veikko; Naimhwaka, Johannes
Abstract : A C 2 -symmetry dianthrimide based probe (D ) and its hydroxide complex (D-OH ) are reported as a chromo-fluorogenic sensor for rapid and sensitive detection of trace amounts of water in polar aprotic solvents. Abstract : A C 2 -symmetry dianthrimide based probe (D ) and its hydroxide complex (D-OH ) are reported as a chromo-fluorogenic sensor for rapid and sensitive detection of trace amounts of water in polar aprotic solvents. Based on intramolecular charge transfer in the excited state, the pink-coloured probe binds with the hydroxide ions to induce a colorimetric response of the resulting complex (D-OH ), green in colour. The hydroxide based complex is used as a H2 O or moisture sensor, tested in DMF and DCM, due to its high instability in moisture-containing organic solvents and paper materials/fabrics. The probe exhibits higher sensitivity towards pure H2 O in DMSO with the LOD measured at 0.0067% v/v, perhaps even lower, in DMF (LOD = 0.100% v/v) and DCM (LOD = 0.013% v/v). The dissociation of OH − from D in the presence of H2 O is responsible for the colorimetric and fluorometric responses. The litmus test paper strips prepared by adsorbing or coating them with the D-OH complex in DMSO could not be entirely achieved in an open system, due to the highly unstable state of the complex in the presence of water traces or the atmospheric moisture accumulated in the paper materials. The complex D-OH is also highly suspected to compete for adsorbed water in silica gel crystals in desiccators, due to its high affinity towards water molecules. The experimental studies were complemented by theoretical calculations using the Spartan'14 software package, and the computed data are in good agreement with the spectral data.